Metric and coupling reversal in string theory - Duff,MJ; Kalkkinen,J (Nuclear Physics B, 2007)
Invariance under reversing the sign of the metric and/or the sign of the string coupling field , where , leads to four possible universes denoted 1, , , according as , , , , respectively. Universe 1 is described by conventional string/M theory and contains all M, D, F and NS branes. Universe contains only , D3 and D7. Universe contains only D1, D5, D9 and Type I. Universe contains only F1 and NS5 of IIB and heterotic SO(32).